Dermatologyphics: comparison between Negritos Orang Asli and the Malays, Chinese and Indian - Ismail, Endom; Abdul Razak, Shairah; Selamat, Lieyana; Gurusamy, Ravindran; Zariman, Hasmarini; Shahrudin, Mohd Shahrizan; Amini, Farhanaz; Bakar, Yosni; Md Nor, Syukor; Osman, Mohamad (Penerbit UKM, 2009)
Dermatoglyphic traits are formed under genetic control during early gestation and do not change through the entire life. A few studies have shown that dermatoglyphic traits were conservative in their evolution and were different between and within population groups. The objective of this study was to compare the variability of palm dermatoglyphs in three main populations i.e. Malay, Chinese, Indian and five sub-ethnic population of Negritos’ Orang Asli i.e. Bateq, Jahai, Kintak, Kensiu and Lanoh. We utilised fingerprints and palms of 390 healthy adult individuals, counted the total ridge for ten fingers (TRC), a-b ridge counts (a-b RC) on palms, examined widening of the atd-angle, and classified the digital pattern configuration of arches, whorls, ulnar, and radial loops for all fingers. Variables obtained from both palm did not show any differences between males and females for all populations. TRC, a-b RC and atd-angle were the highest for Kensiu and were later on specially described to be in a group of its own by ANOVA and TUKEY test for TRC and a-b RC. The same test has put Chinese in a group of its own for atd-angle. Only a-b RC clearly separate Orang Asli populations from the three main races. Whorls and ulnar loops were the most predominant pattern in all groups. Malays and Chinese had similar distributional patterns for each ten fingers. Indian and Jahai similarly mimic each other, while Bateq has the reversal pattern distribution to them both. Kintak and Lanoh halfly mimics each other pattern and Kensiu had its own unique pattern. In conclusion, races, patterns, and pattern frequencies were related to each other and can be used to differentiate different races or Orang Asli sub-ethnics. This study documents for the first time the comparative dermatoglyphic traits between Malaysian main races with Orang Asli populations show a list of informative variables that can be used to identify them as well as suggesting it’s used as a tool in tracing the etnohistorical background of populations.